Oral Health and its Impact on Systemic Diseases: Bridging the Gap Between Dentistry and Public Health - Poudel, Priyanka; Roy, Roshan Kumar; Roy, Deepak Kumar; Mahato, Lalan Kumar; Maharaj, Anuranjan (International Journal of Silkroad Institute of Research and Training, 2025)
Oral health is integral to overall health, with increasing evidence linking oral conditions to systemic diseases such as cardiovascular disease, diabetes, and respiratory infections. Despite this, oral health remains insufficiently integrated into public health policies, particularly in resource-limited settings like Nepal. This cross-sectional study aimed to assess the association between oral health conditions (periodontal disease, dental caries, and oral hygiene practices) and systemic diseases (cardiovascular disease, diabetes, and respiratory infections) among adults in Kathmandu, Nepal. Data were collected from 400 participants through clinical examinations and structured questionnaires that included demographic information, lifestyle factors, and systemic health conditions. The results revealed significant associations between periodontitis and cardiovascular disease (p=0.002), dental caries and uncontrolled diabetes (p=0.01), and poor oral hygiene and respiratory infections (p=0.03). Furthermore, only 25% of participants reported regular dental visits, and awareness of the oral-systemic health connection was low (30%). These findings highlight the need for targeted public health interventions to increase awareness, enhance access to dental care, and integrate oral health into comprehensive healthcare strategies. Addressing oral health alongside systemic health could improve overall health outcomes, alleviate healthcare burdens, and promote a more integrated approach to patient care. Keywords: oral health, systemic diseases, cardiovascular disease, diabetes, respiratory infections, periodontal disease, dental caries, oral hygiene, public health, Nepal.